Konsep Pemikiran Pendidikan Konseptualisasi Pemikiran Pendidikan Islam Klasik-Modern - Zul Adrivat; Wildan Baihaqi; Mimin Tjasmini; Ateng Rohendi; Izzudin Musthafa (Tihamah: Jurnal Studi Islam, 2024)
The development of Islamic education cannot be separated from the development of classical and modern educational thought. The study of classical and modern educational thought aims to rediscover the conceptualization of Islamic educational thought. The hope is that this study can find a common thread in the concepts of classical and modern Islamic education. Previous researchers had many discussions about the study of both, but these discussions ended in the area of ​​examining the thoughts of each figure or were limited to the study of only one period. This research discusses the study of classical and modern educational thought to find out the true meaning in the development of the conceptualization of Islamic educational thought. The method used by the researchers is a literary studies approach. A study approach uses a research view of library documents such as books, magazines, articles, etc. This type of research is classified as descriptive qualitative research. The results of the study show that the development of classical and modern Islamic educational thought represents an inseparable unity. The development of modern Islamic educational thought is part of the development of classical Islamic educational thought. The early phase of educational development can be seen in Islamic teaching at the time of the Prophet. In the period of Mecca and Medina, the Prophet laid the foundations of Islamic education, from the concept, curriculum, tier system and institutions to the administration of Islamic education. Until modern times, the development of Islamic educational thought has shown a maturity in scientific civilization. This can be seen in the birth of Muslim scholars who initiated the integration of knowledge in all fields.